2014
DOI: 10.1126/scisignal.2005283
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral pain is enhanced by insulin-like growth factor 1 through a G protein–mediated stimulation of T-type calcium channels

Abstract: Insulin-like growth factor 1 (IGF-1) is implicated in the nociceptive (pain) sensitivity of primary afferent neurons. We found that the IGF-1 receptor (IGF-1R) functionally stimulated voltage-gated T-type Ca(2+) (CaV3) channels in mouse dorsal root ganglia (DRG) neurons through a mechanism dependent on heterotrimeric G protein (heterotrimeric guanine nucleotide-binding protein) signaling. IGF-1 increased T-type channel currents in small-diameter DRG neurons in a manner dependent on IGF-1 concentration and IGF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(111 citation statements)
references
References 62 publications
3
108
0
Order By: Relevance
“…The phosphorylation sites have been identified in the intracellular domain of IGF-1R, which allow for specific binding and modulation of multiple downstream effectors [27,28]. An earlier study by Wang et al confirmed that low shear stress-induced IGF-1R phosphorylation modulates smooth muscle cell behavior and functions (proliferation and phenotype) via enhancing Akt activation [29].…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 68%
“…The phosphorylation sites have been identified in the intracellular domain of IGF-1R, which allow for specific binding and modulation of multiple downstream effectors [27,28]. An earlier study by Wang et al confirmed that low shear stress-induced IGF-1R phosphorylation modulates smooth muscle cell behavior and functions (proliferation and phenotype) via enhancing Akt activation [29].…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 68%
“…Similar to GH releasing molecules such as ghrelin or GHRH [10,54], IGF-1 and its receptor IGFr1, have also been demonstrated to be involved in nociceptive processing [16,46] in adult rodents possibly by modulating neuronal excitability [74]. Interestingly, in mice overexpressing IGF-2, studies have found reduced sensory innervation of the skin, which may play a role in peripheral responsiveness [52].…”
Section: Gh Regulates Afferent Sensitization Possibly By Suppressing mentioning
confidence: 99%
“…We surprisingly did not detect any differences in the expression of the GH receptor (GHr) in the DRGs of mice inflamed at P7 (−30.6±13%) or P14 (−40.7±23.3%) compared to age-matched naïve DRGs (p>0.05). Our previous data however [24] showed a significant increase in IGFr1 at both ages, which is a known downstream mediator of GH function in other systems [57] and has also been linked to mechanical and thermal hypersensitivity after inflammation [46,74]. Therefore, to test if GH regulated the expression of IGFr1 specifically in sensory neurons, we dissociated P14 DRGs and treated individual cultures with growth hormone.…”
Section: Gh Regulates the Expression Of Igfr1 In Sensory Neuronsmentioning
confidence: 99%
See 2 more Smart Citations